Female genital mutilation : when culture and law clash - Proudman, Charlotte (Oxford : Oxford University Press, 2022)
This is a qualitative study into the impact the criminalisation of female genital mutilation (FGM) has had on diaspora and stakeholder attitudes towards FGM in the UK. It contains survivors' testimonies and explores key themes that emerged from the well-publicised criminal trials in the UK and the barriers that prevent the law from working effectively.
This edition also issued in print: 2022.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from PDF title page (viewed on May 26, 2022).
Keywords: Female circumcision -- Great Britain; Female circumcision -- Law and legislation -- Great Britain; Customs and Folklore; Cultural studies: customs & traditions